ARSENIC EXPOSURE DECREASES ADIPOSITY DURING HIGH-FAT FEEDING - Carmean, Christopher M. (Obesity (Silver Spring), 2020)
OBJECTIVE: Arsenic is an endocrine-disrupting chemical associated with diabetes risk. Increased adiposity is a significant risk factor for diabetes and its comorbidities. Here, the impact of chronic arsenic exposure on adiposity and metabolic health was assessed in mice. METHODS: Male C57BL/6J mice were provided ad libitum access to a normal- or high-fat diet and water +/− 50 mg/L sodium arsenite (iAs). Changes in body weight, body composition, insulin sensitivity, energy expenditure, and locomotor activity were measured. Measures of adiposity were compared to accumulated arsenic in the liver. RESULTS: Despite uniform arsenic exposure, internal arsenic levels varied significantly among arsenic-exposed mice. Hepatic arsenic levels in exposed mice negatively correlated with overall weight gain, individual adipose depots’ masses, and hepatic triglyceride accumulation. No effects were observed in mice on a normal diet. For mice on a high-fat diet, arsenic exposure reduced fasting insulin levels, HOMA-IR, HOMA-β, and systemic insulin resistance. Arsenic exposure did not alter energy expenditure or activity. CONCLUSIONS: Collectively, these data indicate that arsenic is anti-obesogenic, and that concentration at the source poorly predicts arsenic accumulation and phenotypic outcomes. In future studies, investigators should consider internal accumulation of arsenic, rather than source concentration, when assessing the outcomes of arsenic exposure.